On the Horned Cairns of Caithness, their Structural Arrangement, Contents of Chambers, &c (Proceedings of the Society of Antiquaries of Scotland, 1867)
Joseph Anderson continues his analysis of cairns in Caithness as per his previous paper (see Volume 6, pp.442-451). He discusses four long cairns and two short cairns in Caithness, describing their structural characteristics, the interior of each of the cairns and the artefacts found in each one. Several animal bones and some human bones were uncovered during the excavations. He then notes other sites that can be found near these cairns and their similarity to structures in other countries. He concludes with a short discussion about what these sites reveal about the people who built them.